Passeurs de mémoire populaire : Kwani Trust et les lieux de l’histoire - Kate Wallis (Itinéraires)
This article explores the ways in which the Kwani? journal has opened up new forms and spaces for cultural memory. It argues that the editorial agenda of, as well as the work of some of the most prominent voices associated with Kwani Trust as a literary network (including Andia Kisia, Parselelo Kantai, Billy Kahora and Yvonne Adhiambo Owuor), reflects a particular preoccupation with historiography—or the ways in which memory and history are constructed and take form as texts. Setting this in the context of the wider engagement of donor-funded cultural production in Kenya with questions of history and memory in this period, it examines the different ways that these writers confront and explore questions around where knowledge about Kenya’s past is located, who history is produced by and for, and memory’s relationship to literature and material form. Building on and problematizing Jan Assmann’s framing of collective memory as made up of “cultural memory” and “communicative memory,” and putting this in dialogue with Karin Barber’s definitions of “popular arts” (Barber 1987), it characterizes this group of writers as engaged in the construction of popular memory.